A fungal protease named AsES triggers antiviral immune responses and effectively restricts virus infection in arabidopsis and Nicotiana benthamiana plants - Caro, Maria Del Pilar; Venturuzzi, Andrea Laura; Moschen, Sebastian Nicolas; Salazar, Sergio Miguel; Díaz Ricci, Juan Carlos; Asurmendi, Sebastian (Oxford University Press, 2022)
Background and Aims: Plants have evolved complex mechanisms to fight against pathogens. Among these mechanisms, pattern-triggered immunity (PTI) relies on the recognition of conserved microbe- or pathogen-associated molecular patterns (MAMPs or PAMPs, respectively) by membrane-bound receptors. Indeed, PTI restricts virus infection in plants and, in addition, BRI1-associated kinase 1 (BAK1), a central regulator of PTI, plays a role in antiviral resistance. However, the compounds that trigger antiviral defences, along with their molecular mechanisms of action, remain mostly elusive. Herein, we explore the role of a fungal extracellular subtilase named AsES in its capacity to trigger antiviral responses. Methods: In this study, we obtained AsES by recombinant expression, and evaluated and characterized its capacity to trigger antiviral responses against Tobacco mosaic virus (TMV) by performing time course experiments, analysing gene expression, virus movement and callose deposition. Key Results: The results of this study provide direct evidence that exogenous treatment with recombinant AsES increases a state of resistance against TMV infection, in both arabidopsis and Nicotiana benthamiana plants. Also, the antiviral PTI response exhibited by AsES in arabidopsis is mediated by the BAK1/SERK3 and BKK1/SERK4 co-receptors. Moreover, AsES requires a fully active salicylic acid (SA) signalling pathway to restrict the TMV movement by inducing callose deposition. Additionally, treatment with PSP1, a biostimulant based on AsES as the active compound, showed an increased resistance against TMV in N. benthamiana and tobacco plants. Conclusions: AsES is a fungal serine protease which triggers antiviral responses relying on a conserved mechanism by means of the SA signalling pathway and could be exploited as an effective and sustainable biotechnology strategy for viral disease management in plants.